2020
DOI: 10.5539/ijbm.v16n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Accounting and Corporate Sustainability: A Research Synthesis

Abstract: The paper examined the extent of environmental accounting and its relationship with corporate sustainability with an ardent focus on controversies, contradictions, gaps and relationships with previous explorations. The researchers adopted an assiduous literature review approach on the diverse perspectives of investigators and scholars through probing into their conceptualizations, empiricism and theoretical underpinnings of industrialized nations, emerging economies and least developed countries. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In this scenario, hotels are prompted to select EMA practices that in not so long advance financial benefits.69% of the respondents confirmed that EMA practices adopted by their hotel company are mostly hinged on shortterm financial benefits and return. This supports evidence in contemporary literature that EMA is mostly adopted by the corporate sector for financial purposes (Chathurangani & Madhusanka, 2019;Ekundayo & Odhigu, 2021;Gunarathne & Lee, 2015). The respondents explain that the central objective of their business is to attain and increase corporate profitability.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In this scenario, hotels are prompted to select EMA practices that in not so long advance financial benefits.69% of the respondents confirmed that EMA practices adopted by their hotel company are mostly hinged on shortterm financial benefits and return. This supports evidence in contemporary literature that EMA is mostly adopted by the corporate sector for financial purposes (Chathurangani & Madhusanka, 2019;Ekundayo & Odhigu, 2021;Gunarathne & Lee, 2015). The respondents explain that the central objective of their business is to attain and increase corporate profitability.…”
Section: Resultssupporting
confidence: 83%
“…Customers of hotels in Kwazulu Natal are mostly international tourists (Sucheran, 2018). This reiterates the statement that environmental management practices are most popular in developed and industrialized nations (Ekundayo & Odhigu, 2021;Sucheran (2018). Hence, tourists from international countries prefer hotels implementing EMA practices that can be easily identified by them.…”
Section: Resultsmentioning
confidence: 60%